2008
DOI: 10.1093/pcp/pcn154
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Distance, Graft-Transmissible Action of Arabidopsis FLOWERING LOCUS T Protein to Promote Flowering

Abstract: Day length perceived by a leaf is a major environmental factor that controls the timing of flowering. It has been believed that a mobile, long-distance signal called florigen is produced in the leaf under inductive day length conditions, and is transported to the shoot apex where it triggers floral morphogenesis. Grafting experiments have shown that florigen is transmissible from a donor plant that has been subjected to inductive day length to an uninduced recipient plant. However, the nature of florigen has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(103 citation statements)
references
References 41 publications
7
96
0
Order By: Relevance
“…In addition, the movement of FT protein is sufficient to trigger floral initiation, which suggests that the FT protein is a key part of the florigenic signaling pathway. 9,10,[20][21][22][23] Parallel proteomic analyses showed that FT protein is translocated through phloem sap, which is consistent with the notion that the florigen is transported along the phloem translocation stream. 24 Thus, FT protein is clearly part of the florigen.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, the movement of FT protein is sufficient to trigger floral initiation, which suggests that the FT protein is a key part of the florigenic signaling pathway. 9,10,[20][21][22][23] Parallel proteomic analyses showed that FT protein is translocated through phloem sap, which is consistent with the notion that the florigen is transported along the phloem translocation stream. 24 Thus, FT protein is clearly part of the florigen.…”
Section: Introductionsupporting
confidence: 81%
“…Previous Arabidopsis micrografting experiments with young seedlings grafted on hypocotyls failed to detect the movement of FT RNA across the graft junction. 9,23 However, because the trafficking of phloem-mobile RNA is highly dynamic and depends on the sink-source strength between the stock and scion, 27 it is possible that the methods of graft may affect the detection of mobile RNA on the scions. To test this possibility, we used the Arabidopsis cleft-grafting system and continually removed mature leaves from the recipient scion to enhance the translocation of phloem derived from the stock.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin is key to the development of the vascular tissue, and important genes involved in the biosynthesis, transportation, perception, and signaling of this hormone are among PcG targets (Notaguchi et al, 2008;Lafos et al, 2011;Rizzardi et al, 2011). Several genes that play an important role in the auxin pathway are affected in swn clf (Figure 3; see Supplemental Data Set 1 online) (Lafos et al, 2011).…”
Section: Tissue Differentiation Bypasses Lack Of Pcg Repressionmentioning
confidence: 99%
“…Until recently, the biochemical nature of florigen remained elusive until breakthrough experiments in tomato (Solanum lycopersicum; , Arabidopsis thaliana (Corbesier et al, 2007;Jaeger and Wigge, 2007;Notaguchi et al, 2008), and rice (Oryza sativa; Tamaki et al, 2007) revealed that the protein encoded by the FLOWERING LOCUS T (FT) gene had florigenic activity. The FT protein and other related proteins share sequence similarity with mammalian phosphatidylethanolamine binding protein (PEBP) (Kardailsky et al, 1999), which has been annotated as a kinase regulator (Banfield and Brady, 2000).…”
Section: Introductionmentioning
confidence: 99%